2019
DOI: 10.1038/s41416-019-0498-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic effects of crenolanib are mediated by mitotic modulation independently of PDGFR expression

Abstract: BackgroundCrenolanib is a tyrosine kinase inhibitor targeting PDGFR-α, PDGFR-β and Fms related tyrosine kinase-3 (FLT3) that is currently evaluated in several clinical trials. Although platelet-derived growth factor receptor (PDGFR) signalling pathway is believed to play an important role in angiogenesis and maintenance of functional vasculature, we here demonstrate a direct angiostatic activity of crenolanib independently of PDGFR signalling.MethodsThe activity of crenolanib on cell viability, migration, spro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Moreover, although axitinib was designed as a selective VEGFR inhibitor, it has inhibitory effects on more proteins, such as FGFRs Aurora, ABL and MAPK family kinases [39,40]. Indeed, we have recently shown that targeted TKI activity is not always directly related to its designated targets [41]. Additionally, the difference in sensitivity might be explained by slightly different drug target expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although axitinib was designed as a selective VEGFR inhibitor, it has inhibitory effects on more proteins, such as FGFRs Aurora, ABL and MAPK family kinases [39,40]. Indeed, we have recently shown that targeted TKI activity is not always directly related to its designated targets [41]. Additionally, the difference in sensitivity might be explained by slightly different drug target expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Specific VLDL uptake by CD34 - cells may be explained by its role in angiogenesis as a provider of biomass for proliferating stalk cells [ 33 ]. We tested the possible consequences of inhibition of VLDL uptake on the percentage tip cells and on vessel sprouting in the spheroid model.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we have recently discovered that crenolanib, a known PDGFR inhibitor, acts on tumour endothelial cells, a mechanism that is not always directly related to its designated targets. 38 Since resistance to sunitinib is a frequent event in the clinical management of RCC, one way to overcome this challenge is the optimisation of high-order drug mixtures to kill drug-resistant cancer cells. 19,39 Notably, treatment with relatively low-dosed ODCs was effective also in cells chronically pre-treated with sunitinib.…”
Section: Discussionmentioning
confidence: 99%